Benjamin Constant e os gabinetes de Física e Química da Escola Normal da Capital Federal (1890-1892) - Santos, Heloisa Helena Meirelles dos (Revista de História e Historiografia da Educação, 2017)
O objetivo dessa pesquisa é analisar as razões do envolvimento do Governo Provisório republicano, através do ministro Benjamin Constant Botelho de Magalhães, na montagem dos gabinetes de Física e Química da Escola Normal da Capital Federal. Benjamin Constant enviou à Escola Normal uma série de providências relativas a essa empreitada que compreenderam, dentre outras medidas: fazer seguro do prédio escolar, contratar preparador, adequar instalações de gás e disponibilizar recursos do Tesouro para comprar/transportar os equipamentos em momento crítico de instauração do regime republicano. A pesquisa toma por fontes privilegiadas os documentos do acervo do Centro de Memória do Instituto Superior de Educação do Rio de Janeiro, ainda não tratados historiograficamente, que revelaram a participação de Benjamin Constant e uso da máquina governamental para implantação dos gabinetes; a necessidade da compra do material; as discussões dos professores sobre a falta dos gabinetes e indícios do método utilizado no ensino dos normalistas. A investigação conclui que o pertencimento do Ministro Benjamin Constant ao educandário e a meta governamental de civilizar pela Ciência foram as causas do empenho do governo provisório para montagem dos gabinetes na Escola Normal da Capital Federal. Benjamin Constant and the offices of Physics and Chemistry of the Normal School of the Federal Capital (1890-1892). This research aims to analyze the involvement of the Republican Provisional Government, through minister Benjamin Constant Botelho de Magalhães, in the establishment of the Physics and Chemistry offices of the Normal School of the Federal Capital. Benjamin Constant contributed a series of related measures to the Normal School, which included getting an insurance of the school building, recruiting teachers, adjusting gas facilities, and providing Treasury resources to acquire/transport equipment at a critical moment in the establishment of the Republican regime. The privileged sources of this research include documents from the collection of the Center of Memory of the Higher Institute of Education of Rio de Janeiro, not trated historiographically, which revealed the participation of Benjamin Constant and the use of the governmental structure for the establishment of the offices, the need to purchase material, the teachers’ discussions regarding the lack of offices, and indications on the method used in the teaching of normalists. This research shows that Minister Benjamin Constant’s membership in the school and the governmental goal of civilizing through science education were the main causes for the commitment of the Provisional Government in establishing the offices in the Normal School of the Federal Capital. Keywords: History of Education; Normal School of the Federal Capital; Establishment of the Offices of Physics and Chemistry; Benjamin Constant; Republican Scientism.